Hermeneutic Realism: Toward a Truly Meaningful Psychology. Issue 2 (June 2013) - Slife, Brent D.; Christensen, Thane R.
This article presents a brief introduction to a hermeneutic realist approach to psychology, outlining its differences from mainstream psychology in its conceptions of context, change, and possibility. The term "hermeneutic" indicates that psychology's subject matter (e.g., behavior, cognition) is understood more as contextually constituted meanings than as the conventional notion of self-contained objects. The "realism" portion of this phrase implies that this understanding does not devolve to a relativism or subjectivism, but it is grounded in the reality of the world. Hermeneutic realism is not considered a replacement to psychology's current approach but rather is conceptualized and discussed as a needed supplement that leads to new psychological understandings, including new approaches to theory, method, and practice.